Assessing risk attitude: The benefits of pooling measures - Lukas Menkhoff; Sahra Sakha (DIW Economic Bulletin, 2016)
In Germany and many other countries, financial advisors are required by law to assess their clients' risk preferences in order to help them make informed and appropriate investment decisions. Most institutions that provide financial advice-banks, for instance-carry out this assessment using just one type of risk measure. Financial advisors might ask clients to answer a question about their attitudes towards risk, for example, or to choose one option among several more or less risky alternatives. Our study finds, however, that employing only one type of risk measure may result in an inaccurate assessment of risk aversion- and if the underlying information is unreliable, the corresponding investment decision will also be flawed. Based on empirical data comprising an unusually broad set of seven different risk measures, we suggest a more robust risk assessment model that combines various methods. Since our results indicate that these multiple-item risk measures usually outperform single-item measures, we recommend combining two or even three items to obtain more reliable risk attitude profiles. A higher level of accuracy could in turn lead to better investment advice.
Keywords: D8; C93; O12; 330; risk attitude; risk measure; lab-in-the-field experimts; household survey; financial behavior